Coin minting by additive manufacturing and forming - Pragana, João (2021)
Additive manufacturing is proposed as a novel alternative to coin blank's production routes based on rolling, blanking and edge rimming. The presentation draws from laser powder bed fusion of cylinders, slicing into individual coin blanks by electro discharge machining and surface preparation by polishing, to coin minting in a laboratory press-tool system. Special emphasis is given to material deposition and coin minting due to the originality of producing coin blanks with complex intricate contoured holes and to the necessity of subjecting the additive manufactured coin blanks to extreme compressive stresses that are typical of coin minting. Numerical and experimental results confirm the excellent performance of the additive manufactured coin blanks. The new design layouts included in the additive manufactured coin blanks open the way to produce high value-added singular collector coins, which are disruptively different from those available in the market nowadays.